Quality of care and job satisfaction in a Hospital Trust before and after The Coordination Reform in Norway - Irene Aasen Andersen; Ole T. Kleiven; Lars Kyte; Marny Alice Solhaug Pettersen (Wiley, 2020)
Abstract Aims To study the impact of organizational changes on the quality of health services and on health professionals' job satisfaction in specialist health services. Design A repeated cross‐sectional study, including 5 years before (2007) and 5 years after (2017) the introduction of The Coordination Reform in Norway. Methods Nurses and auxiliary nurses working in medical wards at three hospitals evaluated the quality of health services and various aspects of their working conditions, using questionnaires: Quality of Patient Care and the Job Satisfaction Scale. Results In 2017, nurses and auxiliary nurses had longer work experience compared with 2007. Nurses and auxiliary nurses also worked full hours. There was no significant change over time in total Quality of Patient Care score or in any of the sub‐scores. There was no significant change in total Job Satisfaction Scale score over time, but there was a significant decline in the sub‐score for physical working conditions.